Determining the occupational risk level in the task of welding railings in a manufacturing company by means of RULA - Realyvásquez, Arturo (Springer, 2019)
Nowadays, accidents, diseases, injuries, and even deaths, are presented in the manufacturing industry. This is due to a dysergonomic design in the work processes or in workstations, which promotes the appearance of risk factors, such as uncomfortable postures adopted by workers. Then, this research aims to determine the occupational risk level to which employees of a manufacturing company are exposed when they perform the task of welding railing for gardens. To determine the risk level, the RULA and ERIN methods were selected, since they are easy to apply and of low cost. Results indicated that the task of welding railings is highly risky, since the RULA score was 5, whereas the ERIN score was 32, and then, ergonomic interventions are required as soon as possible. Some recommendations are given to decrease the risk level of the task. It is hoped that the company adopts the Ergonomics as a competitiveness strategy.